Distributional analysis of the role of breadth and persistence of multiple deprivation in the health gradient measured by biomarkers - Kompal Sinha; Apostolos Davillas; Andrew M. Jones; Anurag Sharma (University of Essex, Institute for Social and Economic Research (ISER), 2018)
This paper analyses the relationship between health and socioeconomic status accounting for the role of breadth and persistence of multiple deprivation. Adopting a holistic approach to multidimensional deprivation, we construct measures of absolute and relative deprivation and use these measures along with a range of nurse measured and blood-based biomarkers for a distributional analysis of the relationship between socioeconomic status and health. Using data from the British Household Panel Survey and Understanding Society, our analysis finds the presence of systematic multidimensional deprivation gradient across the distribution of most of our biomarkers (BMI, waist circumference, heart rate, C-reactive protein and HbA1c) beyond income, with the size of this gradient to be substantially larger at higher tails of the biomarker distribution. Decomposition analysis of the contribution of components of deprivation to health suggests breadth of deprivation to dominate the contribution over persistence. Health policy prioritising health of people enduring deprivation across multiple domains, i.e., people who experience dual burden of deprivation across several domains and poor health, may be particularly effective at reducing the risk of falling into a health-deprivation trap.
Keywords: C1; C5; D63; I12; I31; 330; biomarkers; multidimensional deprivation; Shapley decomposition